What We’ve Got Here Is Failure to Cooperate: Provincial Governments and the Canadian Reference Power - Puddister, Kate (Revue générale de droit, 2021)
The Canadian reference power provides provincial and federal governments with the ability to seek an advisory opinion from an appellate court on virtually any matter, including the policies of other governments. Because of the great latitude in which governments can wield the reference power, many governments have done so strategically. While the federal reference power was initially created to allow the federal government to oversee the provinces, provincial governments have deployed their own reference power to effectively challenge and resist the actions of the federal government and as a result, have essentially co-opted the original purpose of the reference power. Relying on a systematic analysis of provincially initiated reference cases, including the recent disputes over the Greenhouse Gas Pollution Pricing Act (carbon tax) references, this study demonstrates how the reference power can be a political and strategic tool for subnational governments in a manner that is distinct from the federal government. References can provide provincial governments a means to protect and articulate provincial interests, to voice opposition to the actions of other governments and in some instances, to encourage or reinvigorate negotiation with federal partners. However, this article also demonstrates the limits of the reference power and the use of litigation as a political tool. The reference cases examined here demonstrate that litigation alone cannot force cooperative outcomes.